Flower dependent trafficking of lamellar bodies facilitates maturation of the epidermal barrier - Justin C. Rudd; Jos P. H. Smits; Patrick T. Kuwong; Rachel E. Johnson; Louise M. N. Monga; Ivonne M. J. J. van Vlijmen-Willems; Greer L. Porter; Peter O. Halloran; Kanika Sharma; Karina N. Schmidt; Vikas Kumar; Justin G. Madson; et al. (Nature Communications)
Abstract Specialized secretory cells, including keratinocytes in the last viable layers of mammalian epidermis, utilize lysosome-related organelles (LROs) to exocytose distinct cargoes vital for tissue function. Here, we demonstrate that the Flower isoform, hFWE4, a putative Ca2+ channel that permits endocytic retrieval of presynaptic vesicles and lytic granules, also resides on epidermal lamellar bodies (LBs), an LRO that extrudes a proteinaceous lipid-rich matrix to finalize the epidermal barrier. In differentiated keratinocyte cultures, we show that hFWE4-positive LB-like vesicles associate with a distinct ensemble of LRO trafficking mediators and demonstrate that hFWE4 liberates Ca2+ from intracellular stores to enable the surface presentation of cargo contained within these vesicles. Finally, supporting a critical role for hFWE4-dependent trafficking in establishing the epidermal barrier, we demonstrate that this process is dysregulated in genetic diseases of cornification that are driven by impairments in keratinocyte Ca2+ handling. Our results provide new insight into the biogenesis and trafficking of epidermal LBs and more broadly suggest that hFWE4 may serve as a core component of LRO trafficking machinery that endows Ca2+ dependency to distinct stages of the transport process depending on the cell of origin.